Semi-Automatic Fertilizer Sprayer V2023 - M. Haikal Fauzi; Aliff Danial M. Faizal; M. Nasrin M. Sabri; Janon, Mohd Najib; Mahmod Abd Hakim Mohamad; Abdullah Wagiman (Multidisciplinary Applied Research and Innovation, 2023)
Liquid fertilizers are very important in maintaining nutrients for the plants. These fertilizers are commonly applied by using a knapsack sprayer. The usages of knapsack sprayer are low in safety, which can lead to muscular fatigue and pain on the leg, upper arm left and the neck. To address this problem, Semi-Automatic Fertilizer Sprayer is developed by remove load of fertilizer in the knapsack and introduce new design based on wheelbarrow concept. Hence, in this project, various concepts of semi-automatic fertilizer sprayer are compared in many aspects and parameters. Concept and parametric design are developed and analyzed according to the performance, structure construction and development costing. These tools aim to be able to spray the fertilizer without manually pumping it, reduce time consumption and minimize required energy while using this sprayer. This paper also present key findings or trend from experiment data and summarize the discussion based on findings.